2003
DOI: 10.1128/jb.185.21.6477-6480.2003
|View full text |Cite
|
Sign up to set email alerts
|

Thymine at —5 Is Crucial for cpc Promoter Activity of Synechocystis sp. Strain PCC 6714

Abstract: The levels of transcripts of the cpc operon were highly reduced in a PD-1 mutant of cyanobacterium Synechocystis sp. strain PCC 6714. This was due to a substitution of C for T that occurred at 5 bp upstream of the transcription initiation site of the cpc operon. Any substitution for T at the ؊5 position drastically reduced both in vivo and in vitro promoter activity in cyanobacterium Synechococcus sp. strain PCC 7942 but not the in vivo activity in Escherichia coli. This suggests that the requirement of ؊5T ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
(14 reference statements)
0
28
0
Order By: Relevance
“…2). The P cpc promoter of the cpc operon, which encodes the photosynthesis antenna protein phycocyanin (26), and the P rbc promoter of the rbc operon, which encodes ribulose 1,5-bisphosphate carboxylase (27), both drive highly expressed genes in SD100. In SD223 and SD225, two poly-3-hydroxybutyrate (PHB) synthesis genes (slr1993 and slr1994) were deleted.…”
Section: Resultsmentioning
confidence: 99%
“…2). The P cpc promoter of the cpc operon, which encodes the photosynthesis antenna protein phycocyanin (26), and the P rbc promoter of the rbc operon, which encodes ribulose 1,5-bisphosphate carboxylase (27), both drive highly expressed genes in SD100. In SD223 and SD225, two poly-3-hydroxybutyrate (PHB) synthesis genes (slr1993 and slr1994) were deleted.…”
Section: Resultsmentioning
confidence: 99%
“…S3). Therefore, the same nucleotide substitution and an additional T→G substitution, which has also been shown to lower transcription (Imashimizu et al, 2003), were introduced into the wild type and the DCpcC2 and DCpcC1C2 mutants via two-step homologous recombination. The promoter region around the T nucleotide was first replaced with an npt1/ sacRB cassette.…”
Section: Generation Of Recombinant Strains Of Synechocystis Sp Pcc 6803mentioning
confidence: 99%
“…A Synechocystis sp. PCC 6714 mutant with a T→C substitution 5 bp downstream of the transcription initiation site of the cpcBAC1C2D operon (PD-1; Imashimizu et al, 2003) and containing only one-third the level of PC (Nakajima et al, 1998) demonstrated reduced photoinhibition and 20% to 30% higher photosynthesis, as determined by higher oxygen evolution rates, in dense cultures under high light (Nakajima and Ueda, 1997). However, biomass accumulation and growth were not quantified in these studies.…”
mentioning
confidence: 99%
“…The site was mapped 251 bp upstream from the translation start for cpcB in Synechocystis sp. strain PCC6714 (Imashimizu et al, 2003), a strain that is closely related to Synechocystis sp. strain PCC6803.…”
Section: Discussionmentioning
confidence: 99%